2016
DOI: 10.1007/s10461-016-1656-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed HIV Infection in Transgender Adults and Adolescents: Results from the National HIV Surveillance System, 2009–2014

Abstract: Publications on diagnosed HIV infection among transgender people have been limited to state- or local-level data. We analyzed data from the National HIV Surveillance System and present results from the first national-level analysis of transgender people with diagnosed HIV infection. From 2009 to 2014, HIV surveillance jurisdictions from 45 states plus the District of Columbia identified and reported at least one case of newly diagnosed HIV infection for transgender people; jurisdictions from 5 states reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
110
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 35 publications
(26 reference statements)
3
110
0
Order By: Relevance
“…For example, in several African countries, depression, condomless receptive anal sex, law enforcement stigma and violence were significantly associated with HIV . In the United States and Peru , race, multiple sexual partners, condomless receptive anal or vaginal sex, non‐prescribed injection of hormones or drugs, sharing drug paraphernalia, engaging in commercial sex work and history of sexually transmitted infections (STI) were associated with HIV . In Southeast Asia, age, alcohol use, amphetamine use, sex with male sex workers and dressing as a woman all the time were risk factors for HIV .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in several African countries, depression, condomless receptive anal sex, law enforcement stigma and violence were significantly associated with HIV . In the United States and Peru , race, multiple sexual partners, condomless receptive anal or vaginal sex, non‐prescribed injection of hormones or drugs, sharing drug paraphernalia, engaging in commercial sex work and history of sexually transmitted infections (STI) were associated with HIV . In Southeast Asia, age, alcohol use, amphetamine use, sex with male sex workers and dressing as a woman all the time were risk factors for HIV .…”
Section: Introductionmentioning
confidence: 99%
“…. Of 2351 transgender individuals identified in the National HIV Surveillance System with newly diagnosed HIV infection during 2009–2014, 84.0% were TGW (male-to-female) (6). In particular, TGW (male-to-female) youth of color have been identified as at extreme risk of acquiring HIV (7).…”
Section: Introductionmentioning
confidence: 99%
“…Between 2009 and 2014 in the U.S., more than one in 3 diagnoses in TF individuals were ages 13–24 years (8.3% ages 13–19 years, 28.0% ages 20–24 years); more than one in 5 were in TM (6.4% age 13–19, 16.6% ages 30–24) [20]. Community-based convenience samples have reported HIV prevalence between 5 [21, 22] and 20% [23, 24] in TF under ages 29 years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to our knowledge, there has been very limited research on HIV and related outcomes in nonbinary individuals (e.g., gender nonconforming, genderqueer, genderfluid, or any other gender different than their assigned sex at birth), either youth or adults. National HIV Surveillance System data from 2009 to 2014 found that 0.7% of HIV infections (n = 16) occurred in nonbinary transgender people; however, data were not disaggregated by other factors (e.g., age, sex assigned at birth, race, ethnicity) [20]. These data are urgently needed to reduce HIV incidence and improve health outcomes for diverse TG youth who are vulnerable to and living with HIV infection.…”
Section: Introductionmentioning
confidence: 99%